Implementation of Social and Environmental Responsibility of PT Pelabuhan Indonesia (Persero) Sub Regional Kalimantan - Erpansyah; Tino Kemal Fattah (Magister Administrasi Bisnis ULM, 2024)
Abstract: This research aims to examine the implementation of social and environmental responsibility (TJSL) by PT Pelabuhan Indonesia (Persero) in the Kalimantan sub-region, focusing on the allocation, increase, and decrease in budget percentages available annually from 2020 to 2022. The study employs a qualitative research method. To obtain accurate information, data were collected through semi-structured interviews and documentation, including document collections, transcripts, books, journals, and other relevant materials. Data analysis techniques involved reviewing all available data from various sources, such as interviews, observations recorded in field notes, documents, and more, leading to the drawing of conclusions. The research findings indicate that the realization of funds and available budget for TJSL at PT Pelabuhan Indonesia (Persero) in the Kalimantan sub-region shows varying percentages of fund realization across different partnership programs, with a decrease observed annually. Conversely, the community development programs have shown an annual increase in their budgets. This study highlights the dynamic nature of fund allocation in TJSL initiatives and underscores the need for continuous evaluation and strategic planning Keywords: Implementation, Social and Environmental Responsibility